1989
DOI: 10.3354/dao006145
|View full text |Cite
|
Sign up to set email alerts
|

Densonucleosis of bloodsucking mosquitoes

Abstract: Ultrastructure, development and histopathology of a new densonucleosis vlrus of bloodsucking mosquitoes are described. Mosquito densonucleosis virus is infective to all 4 larval instars, pupae and adults of both sexes. Incubation periods were significantly shorter in older fourth-instar larvae than in third-instar larvae. Infected larvae die during the fourth larval instar or as pupae. The limited field tests conducted on this virus have shown its efficiency for infecting larvae of natural mosquito populations. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
30
1

Year Published

1995
1995
2011
2011

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 7 publications
2
30
1
Order By: Relevance
“…A baculovirus may prove useful in the control of Culex mosquitoes (Becnel et al 2001). The Aedes densonucleosis virus (family Parvoviridae, genus Brevidensovirus, AeDNV) was originally isolated in the Ukraine (Lebedeva et al 1972) and also has potential as a biological control agent (Buchatsky 1989). AeDNV has been extensively characterized with respect to its host range and has been found to be highly speciÞc to mosquitoes of the Aedes and Culex genera.…”
mentioning
confidence: 99%
“…A baculovirus may prove useful in the control of Culex mosquitoes (Becnel et al 2001). The Aedes densonucleosis virus (family Parvoviridae, genus Brevidensovirus, AeDNV) was originally isolated in the Ukraine (Lebedeva et al 1972) and also has potential as a biological control agent (Buchatsky 1989). AeDNV has been extensively characterized with respect to its host range and has been found to be highly speciÞc to mosquitoes of the Aedes and Culex genera.…”
mentioning
confidence: 99%
“…The type species of the genus Brevidensovirus is Aedes aegypti densovirus (AaeDNV) (Buchatsky., 1989). The genus contains several other isolates including Aedes albopictus densovirus (AalDNV) [this species contains to date three distinct viruses from C6/36 cells all identified as AalDNV, we shall refer to these in this paper as AalDNV-1 (identified by Jousset et al, 1993;Boublik et al, 1994), AalDNV-2 (identified by Chen et al, 2004) and AalDNV-3 (identified by Paterson et al, 2005)].…”
mentioning
confidence: 99%
“…caspius, and to a lesser extent Culex pipiens. 10 AaPV is highly pathogenic for Ae. aegypti, killing up to 95% of larvae after oral infection.…”
mentioning
confidence: 99%